2013
DOI: 10.1074/jbc.m112.442053
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Human Angiotensin II Type 1 (AT1) Receptor Bound to Angiotensin II from Multiple Chemoselective Photoprobe Contacts Reveals a Unique Peptide Binding Mode

Abstract: Background: G protein-coupled receptors (GPCRs) modulate a plethora of physiological processes. Results: The determination of 38 ligand/receptor contacts enabled the evidence-based modeling of a GPCR structure. Conclusion: The proposed GPCR structure assumes four interaction clusters with its ligand, which adopts a vertical binding mode. Significance: Elucidating the structure of GPCRs is central to their understanding and has several implications, e.g. rational drug design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
35
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 68 publications
15
35
0
9
Order By: Relevance
“…A two-step model for binding of AngII to AT 1 receptor has been proposed (Le et al, 2002;Feng et al, 2005). Boucard et al (2000) suggested an extended conformation of AT 1 receptorbound AngII (Perodin et al, 2002;Fillion et al, 2013). The methionine proximity mapping approach they used identified details of the residues lining the AngII binding (Correa et al, 2002;Clement et al, 2005Clement et al, , 2006Clement et al, , 2009.…”
Section: A Structure-functionmentioning
confidence: 99%
“…A two-step model for binding of AngII to AT 1 receptor has been proposed (Le et al, 2002;Feng et al, 2005). Boucard et al (2000) suggested an extended conformation of AT 1 receptorbound AngII (Perodin et al, 2002;Fillion et al, 2013). The methionine proximity mapping approach they used identified details of the residues lining the AngII binding (Correa et al, 2002;Clement et al, 2005Clement et al, , 2006Clement et al, , 2009.…”
Section: A Structure-functionmentioning
confidence: 99%
“…Ang II initially binds to ECL to induce a change in the ECL conformation to set a motion of ECLs to cause movements of the TM helices that in turn cause conformational changes in the cytoplasmic domain to initiate signal transduction . The involvement of the amino terminal and all three ECLs of the AT 1 receptor in the binding of Ang II suggest a relatively large surface area for the recognition of peptides (Fillion et al 2013 (Fillion et al 2010). Klco et al (2006) have identified a conserved structural motif, WPFG (Trp94, Pro95, Phe96, and Gly97) within the first ECL.…”
Section: Extracellular Loopsmentioning
confidence: 99%
“…Disruption of both of the disulfide bonds nearly completely abolished Ang II binding to the AT 1 receptor, suggesting the contribution of the disulfide bonds to the maintenance of the binding conformation . The extracellular disulfide bridges in conjunction with a b-hairpin fold in ECL2 appeared to shape the entrance of the ligand-binding site by maintaining in close vicinity the residues of the ECL2 that are important for ligand binding and functions (Fillion et al 2013). ECL2 is the site for glycosylation.…”
Section: Extracellular Loopsmentioning
confidence: 99%
See 2 more Smart Citations